Accuracy of Intravascular Ultrasound-Based Fractional Flow Reserve in Identifying Hemodynamic Significance of Coronary Stenosis. (February 2021) - Yu, Wei; Tanigaki, Toru; Ding, Daixin; Wu, Peng; Du, Haiyan; Ling, Li; Huang, Biao; Li, Guanyu; Yang, Wei; Zhang, Su; Yan, Fuhua; Okubo, Munenori; et al.
Abstract : Background: Ultrasonic flow ratio (UFR) is a novel method for fast computation of fractional flow reserve (FFR) from intravascular ultrasound images. The objective of this study is to evaluate the diagnostic performance of UFR using wire-based FFR as the reference. Methods: Post hoc computation of UFR was performed in consecutive patients with both intravascular ultrasound and FFR measurement in a core lab while the analysts were blinded to FFR. Results: A total of 167 paired comparisons between UFR and FFR from 94 patients were obtained. Median FFR was 0.80 (interquartile range, 0.68–0.89) and 50.3% had a FFR⩽0.80. Median UFR was 0.81 (interquartile range, 0.69–0.91), and UFR showed strong correlation with FFR ( r =0.87; P <0.001). The area under the curve was higher for UFR than intravascular ultrasound-derived minimal lumen area (0.97 versus 0.89, P <0.001). The diagnostic accuracy, sensitivity, specificity, positive predictive value, negative predictive value, positive likelihood ratio, and negative likelihood ratio for UFR to identify FFR⩽0.80 was 92% (95% CI, 87–96), 91% (95% CI, 82–96), 96% (95% CI, 90–99), 96% (95% CI, 89–99), 91% (95% CI, 93–96), 25.0 (95% CI, 8.2–76.2), and 0.10 (95% CI, 0.05–0.20), respectively. The agreement between UFR and FFR was independent of lesion locations ( P =0.48), prior myocardial infarction ( P =0.29), and imaging catheters ( P =0.22). Intraobserver and interobserver variability of UFR analysis was 0.00±0.03 and 0.01±0.03, respectively. Median UFR analysis time was 102 (interquartile range, 87–122) seconds. Conclusions: UFR had a strong correlation and good agreement with FFR. The fast computational time and excellent analysis reproducibility of UFR bears the potential of a wider adoption of integration of coronary imaging and physiology in the catheterization laboratory. Abstract : Supplemental Digital Content is available in the text.